The Effect of Website Content, Its Perceived Usefulness and Perceived Ease of Use towards Customer Purchase Intention: Evidence From Love Bonito - Sari, Mira; Depari, Genesis Sembiring (PT FORMOSA CENDEKIA GLOBAL, 2023)
The goal of this study is to determine which of perceived utility, perceived usability, and website content has an impact on Love, Bonito's customers' intention to make a purchase. Additionally, it will investigate whether these three variables will have an impact on customers' intentions to buy. Data were gathered by questionnaires and the convenience sampling method as part of the quantitative data analysis method used in this study. Following the use of the Lemeshow formula, responses from 97 respondents were received. The outcome of the hypothesis test demonstrates that while website content has no influence on customers' intentions to make a purchase, perceived utility and perceived usability do. However, all three criteria simultaneously affect a customer's intent to buy. Additionally, the coefficient of determination test result reveals that 35.7% of the variables that affect purchase intention in this study are independent variables.The goal of this study is to determine which of perceived utility, perceived usability, and website content has an impact on Love, Bonito's customers' intention to make a purchase. Additionally, it will investigate whether these three variables will have an impact on customers' intentions to buy. Data were gathered by questionnaires and the convenience sampling method as part of the quantitative data analysis method used in this study. Following the use of the Lemeshow formula, responses from 97 respondents were received. The outcome of the hypothesis test demonstrates that while website content has no influence on customers' intentions to make a purchase, perceived utility and perceived usability do. However, all three criteria simultaneously affect a customer's intent to buy. Additionally, the coefficient of determination test result reveals that 35.7% of the variables that affect purchase intention in this study are independent variables.